Respiratory Parameter Has A Great Impact in Determining Sepsis Condition in COVID-19 Patients at Saiful Anwar Hospital Malang: Case Report - Timuda, Caesar Ensang; Setyawan, Ungky Agus; Djajalaksana, Susanthy (RSUP Dr. Kariadi, 2020)
To describe Sequential Organ Failure Assessment (SOFA) Score parameters which have a great impact in the condition of sepsis in Corona Virus Disease-19 (COVID-19) patients and comorbidities that aggravate the patient's condition, we conducted a prospective cohort study in adult patients with sepsis and confirmed COVID-19 cases. We conducted a prospective cohort study in confirmed COVID-19 patients with sepsis who were admitted at Saiful Anwar Hospital Malang at March 10th–April 21st 2020. Diagnosis of sepsis is based on the Surviving Sepsis Campaign-III criteria. We found 6 COVID-19 confirmed patients with sepsis. There is an increased respiratory parameter in SOFA Score in these patients. Therefore, respiratory parameter of the SOFA score has a great impact in determining sepsis condition among confirmed COVID-19 patients. Keywords: COVID-19, Sepsis, SOFA Score